Struktur Tari Bubu di Sanggar Tari Putri Kelana Kabupaten Penukal Abab Lematang Ilir (PALI) - Sumantri, Pino; Rochayati, Rully; Hasan, Hasan (Institut Teknologi Pendidikan Indonesia, 2022)
Abstract Bubu Dance is a new creation dance in Putri Kelana Dance Studio, Penukal Abab Lematang Ilir Regency, created in 2018. The problem formulation in this study is